Perbandingan inovasi strategi perbankan di Indonesia di lingkungan industri kompetitif - Wijayanti, U’ut; Mawadda, Alfia Aulia; Nurdin, Annisa Putri (Maliki Interdisciplinary Journal, 2023)
Strategy is defined as the process of determining how a company will move forward by creating a vision and mission. The strategy created must be in accordance with the company’s goals to create the best conditions for the company. The banking sector is the subject of this research, with PT Bank Capital Tbk, PT Bank BTPN Tbk, and PT Bank Mandiri Taspen as samples. The aim of this research is to find strategic differences between PT Bank Capital Tbk, PT Bank BTPN Tbk, and PT Bank Mandiri Taspen. The research method used is a case study, and the data used is secondary data. To survive in a competitive business environment, this research shows that effective strategic management is essential. The analysis shows that every one of the three companies has a different management strategy that allows them to survive.